Olympic lightweight and open-class rowers possess distinctive physical and proportionality characteristics - Kerr, D. A.; Ross, W. D.; Norton, K.; Hume, P.; Kagawa, M.; Ackland, T. R. (Journal of Sports Sciences, 2007)
Rowers competing at the 2000 Olympic Games were measured for 38 anthropometric dimensions. The aim was to identify common physical characteristics that could provide a competitive advantage. The participants included 140 male open-class rowers, 69 female open-class rowers, 50 male lightweight rowers, and 14 female lightweight rowers. Body mass, stature, and sitting height were different (P < 0.01) between the open-class and lightweight rowers, as well as a comparison group of healthy young adults ("non-rowers", 42 males, 71 females), for both sexes. After scaling for stature, the open-class rowers remained proportionally heavier than the non-rowers, with greater proportional chest, waist, and thigh dimensions (P < 0.01). Rowers across all categories possessed a proportionally smaller hip girth than the non-rowers (P < 0.01), which suggested the equipment places some constraints on this dimension. Top-ranked male open-class rowers were significantly taller and heavier and had a greater sitting height (P < 0.01) than their lower-ranked counterparts. They were also more muscular in the upper body, as indicated by a larger relaxed arm girth and forearm girth (P < 0.01). For the male lightweight rowers, only proportional thigh length was greater in the best competitors (P < 0.01). In the female open-class rowers, skinfold thicknesses were lower in the more highly placed competitors (P < 0.01). In conclusion, the rowers in this sample demonstrated distinctive physical characteristics that distinguish them from non-rowers and other sports performers.